Hate Trumps Love: The Impact of Political Polarization on Social Preferences - Eugen Dimant (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Political polarization has ruptured the fabric of U.S. society. I quantify this phenomenon through the use of 5 pre-registered studies, comprising 15 behavioral experiments and a diverse set of over 8,600 participants. The focus of this paper is to examine various behavioral-, belief-, and norm-based layers of (non-)strategic decision-making that are plausibly affected by existing polarization in the context of Donald J. Trump. I find strong heterogeneous effects: ingroup-love occurs in the perceptional domain (how close one feels towards others), whereas outgroup-hate occurs in the behavioral domain (how one helps/harms/cooperates with others). The rich setting also allows me to examine the mechanisms of observed intergroup conflict, which can be attributed to one's grim expectations regarding cooperativeness of the opposing faction, rather than one's actual unwillingness to cooperate. In a final step, I test whether popular behavioral interventions (defaults and norm-nudging) can eradicate the detrimental impact of polarization in the (non-) strategic contexts studied here. The interventions are ineffective in closing the polarization gap, suggesting that structural – on top of behavioral - changes are needed to mend existing fractions and heal the society.
Keywords: C90; D01; D90; 330; identity; norms; nudging; polarization; social preferences